A Debt Overhang Model for Low-Income Countries : Implications for Debt Relief - Koeda, Junko (IMF Working Papers; Working Paper ;, 2006)
The paper presents a theoretical model to explain how debt overhang is generated in low-income countries and discusses its implications for debt relief. The paper indicates that the extent of debt overhang, and the effectiveness of debt relief, would depend on a recipient country's initial economic conditions and level of total factor productivity.